Comparison of the NBM 200 non-invasive haemoglobin sensor with Sahli’s hemometer among adolescent girls in rural India - Ahankari, Anand S.; Dixit, J.V.; Fogarty, Andrew W.; Tata, Laila J.; Myles, Puja R. (BMJ, 2016)
Objective: The study objective was to compare haemoglobin measurements between the NBM 200 (non-invasive haemoglobin sensor) and Sahli’s hemometer in adolescent girls in a rural Indian setting.